ANALYSIS OF INTERNAL FACTORS AFFECTING EXTERNAL AUDIT QUALITY EMPIRICAL STUDY ON LQ 45 COMPANIES ON THE INDONESIA STOCK EXCHANGE - Harry Budiantoro; Perdana Wahyu Santosa; Kanaya Lapae; Irwin Ananta Vidada (Jurnal Ekonomi, 2022)
The development of audit services in Indonesia is considered to be getting better, accompanied by a positive increase in demand-supply making audit services more attractive to entities as users. This study aims to determine the effect of auditor specialization, tenure, KAP size, time and budget pressure, rotation, and audit fees on audit quality. Data were taken from LQ 45 companies listed on the Indonesia Stock Exchange for the period 2012-2018 which were analyzed by logistic regression. This study found that KAP size significantly affects audit quality, while other variables are not proven, and overall all variables simultaneously affect audit quality